Comparison of efficacy, safety, and cost-effectiveness of various statins in dyslipidemic diabetic patients - Bener, Abdulbari; Dogan, Muzeyyen; Barakat, Lolwa; Al-Hamaq, Abdulla O. A. A. (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2014)
Background and Aim: To determine efficacy safety and the cost effectiveness, of the four most commonly prescribed statins (rosuvastatin, atorvastatin, pravastatin, and simvastatin) in the treatment of dyslipidemia among diabetic patients. Materials and Methods: This is a cohort, observational, population-based study conducted at diabetic clinics of the Hamad Medical Hospital and Primary Health Care Centers (PHCC) over a period from January 2007 to September 2012. The study included 1,542 consecutive diabetes patients above 18 years of age diagnosed with dyslipidemia and prescribed any of the indicated statins. Laboratory investigations were taken from the Electronic Medical Records Database (EMR-viewer). The sociodemographic, height, weight, and physical activities were collected from Patients Medical Records. Information about statin was extracted from the pharmacy drug database. The effective reductions in total cholesterol using rosuvastatin with atorvastatin, simvastatin, and pravastatin in achieving cholesterol goals and improving plasma lipids in dyslipidemic diabetic patients were measured. Serum lipid levels measured a 1 week before the treatment and at the end 2 (nd) year. Results: Rosuvastatin (10 mg) was the most effective in reducing low-density lipoprotein cholesterol (LDL-C; 28.59%), followed by simvastatin 20 mg (16.7%), atorvastatin 20 mg (15.9%), and pravastatin 20 mg (11.59.3%). All statins were safe with respect to muscular and hepatic functions. Atorvastatin was the safest statin as it resulted in the least number of patients with microalbuminuria (10.92%) as compared to other statins. Treatment with rosuvastatin 10 mg was more effective in allowing patients to reach European and Adult Treatment Plan (ATP) III LDL-C goals as compared to other statins (P < 0.0001) and produced greater reductions in LDL-C, total cholesterol, and non-HDL-C, produced similar or greater reductions in triglycerides (TGs) and increased in HDL-C. Conclusion: Rosuvastatin 10 mg was the most effective statin in reducing serum lipids and total cholesterol in dyslipidemic diabetic patients.
Keywords: Atorvastatin; cost effective; dyslipidemic diabetic patients; efficacy; pravastatin; rosuvastatin; safety of statin use in dyslipidemic diabetic patients; safety; simvastatin; HIGH-RISK; CHOLESTEROL GOALS; LIPID GOALS; POPULATION; PREVALENCE; EVALUATE; Pharmacology & Pharmacy